Prestasi Akademik Mahasiswa Aktivis Organisasi Kemahasiswaan pada Prodi D3 Kebidanan Fakultas Kedokteran Undiksha - I Ketut Wijana; Ria Tri Harini Dwi Rusiawati (ProHealth Journal, 2025)
Students have a strategic role in shaping the future of the nation, and in addition to academic activities, they are often involved in student organizations that provide benefits in developing leadership skills, time management, and social abilities. Students who are active in organizations often face a dilemma in dividing time between organizational activities and academic tasks that must be completed, which can interfere with concentration in learning. Methods: This study used a descriptive method with a quantitative approach, with the subject of active students in the student organization of the Midwifery Study Program of FK Undiksha. Determination of research subjects using purposive sampling technique, with a total sample of 94 respondents. Data were collected through interviews with questionnaires and documentation of students' Achievement Index (IP). Data is processed simply by using percentile techniques. Results: almost all students (99%) joined the organization because of their own desires, and most (55%) had previous organizational experience. All parents supported students' involvement in organizations (100%), and most parents had also been involved in organizations (57%). During the exam quiet week, the majority of students (76%) chose not to participate in organizational activities. Most students (95%) chose their majors based on their own desires, and 29% performed well in high school. In addition, 61% of students reported an increase in their grade point average (GPA) while being active in the organization. Conclusion: student involvement in student organizations has a positive impact on self-development and academic achievement. Family support is a very important factor in motivating and managing time between academic and organizational activities.